Radion Production in High Energy Photon Collisions - Giang, Bui Thi Ha; Soa, Dang Van; Thuy, Dao Thi Le (Communications in Physics, 2017)
We study the Higgs-radion mixing and photon collisions. We consider the radion production in high energy photon collisions to search for the radion in the Randall-Sundrum model. Numerical evaluation gives observable cross-section in the future colliders.